Comparison of Financial Performance Before and During COVID-19: Case Study of Hospitality Business, Indonesia - Malikah, Anik (Golden Ratio of Finance Management, 2021)
This study aims to determine and analyze whether there are differences between financial performance before and during the COVID-19 pandemic in hotel companies listed on the Indonesia Stock Exchange for the 2019-2020 period. The financial ratios used are liquidity ratios, solvency ratios, activity ratios, and profitability ratios. The population in this study is an industrial service company engaged in the hospitality sector for the 2019-2020 period. Sampling was done by the purposive sampling method. So, we obtained seven companies as samples. The data analysis method used is the paired sample t-test. The study result states First, the liquidity ratio of companies engaged in the hospitality sector is significantly different. Second, the solvency ratio of companies engaged in the hospitality sector did not differ significantly. Third, the activity ratio of companies engaged in the hospitality sector did not differ significantly. Fouth, the profitability ratios of companies engaged in the hospitality sector were not significantly different. This means that there is a difference in the company's profitability ratios. However, it did not have a significant effect before and during the COVID-19. This is seen from the analysis of the solvency ratios, which show that the three ratios used have a downward trend.